Development and Clinical Application of a Recombinase Polymerase Amplification-Lateral Flow Strip Assay for Detection of Carbapenem-Resistant Acinetobacter baumannii - Wang, Lei; Sun, Dunpo; Chen, Li; Zhou, Ping; Wang, Kun; Wang, Fang; Lei, Xingqi; Wang, Yan; Lu, Yingzhi; Huang, Guanhong; Gao, Xuzhu (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Acinetobacter baumannii is a worldwide, primary cause of respiratory tract infections, septicemia, urinary apparatus infections, and secondary meningitis. It can be fatal. Rapid and accurate detection methods are needed to control the spread of carbapenem-resistant A. baumannii (CRAB). Current molecular diagnostic methods are limited and not suitable for on-site detection. In this study, an isothermal detection method using recombinase polymerase amplification (RPA) combined with a lateral flow strip (LFS) was developed to target the blaOXA-51 and blaOXA-23 genes of A. baumannii. The reaction was completed in about 40 min at 37°C. This method can also effectively distinguish A. baumannii and CRAB. The limit of detection of 100-101 CFU/reaction was equal to that of other detection methods. The detection accuracy was equal to that of the qPCR method with the use of clinical samples. The RPA-LFS assay is portable, rapid, and accurate and could replace existing detection methods for on-site detection of A. baumannii and CRAB.